Neuropsychological tests are useful for predicting comorbidities of idiopathic normal pressure hydrocephalus. (19th July 2020) - Kamohara, Chihiro; Nakajima, Madoka; Kawamura, Kaito; Akiba, Chihiro; Ogino, Ikuko; Xu, Hanbing; Karagiozov, Kostadin; Arai, Hajime; Miyajima, Masakazu
Abstract : Objectives: Comorbidities of idiopathic normal pressure hydrocephalus (iNPH), such as Alzheimer's disease (AD) and Parkinson's spectrum (PS) disorder, can affect the long‐term prognosis of cerebrospinal fluid (CSF) shunting. Therefore, it is important to be able to predict comorbidities in the early stage of the disease. This study aimed to predict the comorbidities of iNPH using neuropsychological tests and cognitive performance evaluation. Materials & Methods: Forty‐nine patients with possible iNPH were divided into three groups: iNPH without AD or PS comorbidity (group‐1), iNPH with AD comorbidity (group‐2), and iNPH with PS comorbidity (group‐3), according to CSF biomarkers such as phosphorylated tau and dopamine transporter imaging. Scores on the new EU‐iNPH‐scale, which is based on 4 neuropsychological tests (Rey Auditory Verbal Learning Test, Grooved Pegboard test, Stroop colour‐naming test and interference test), were compared for each group. In addition, the scores before and 12 months after CSF shunting for each group were compared. Results: EU‐iNPH‐scale using 4 neuropsychological tests could distinguish group‐1 from group‐2 or group‐3 by area under the curve values of 0.787 and 0.851, respectively. Patients in group‐1 showed a remarkable increase in memory and learning ability after surgery. Group‐2 performed significantly poorer than group‐1 patients on memory testing, but otherwise showed improvements in most of the neuropsychological tests. Group‐3 performed significantly worse than group‐1 patients—especially on Stroop tests—but showed post‐surgery improvement on only the Stroop colour‐naming test. Conclusions: The 4 neuropsychological tests of the EU‐iNPH‐scale can help predict iNPH comorbidities and evaluate the prognosis of CSF shunting.